1994
DOI: 10.1063/1.467871
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of rotational and vibrational relaxation in methane overtone levels by time-resolved infrared double-resonance spectroscopy

Abstract: A time-resolved infrared double-resonance technique has been used to measure vibrationally and rotationally inelastic collision rates in ground and vibrational overtone levels of methane. A Raman-shifted Ti:sapphire laser is used to pump J=0 through 7 states in the 2ν3 and ν3+ν4 levels of 12CH4, and a tunable diode laser is used to probe the time-dependent level populations. Vibrational equilibration is observed among the octad, pentad, and dyad levels, with subsequent relaxation to the ground state. State-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…It was believed until recently that vibrational relaxation in hydrocarbon molecules proceeds rather rapidly, and the translational, rotational, and vibrational degrees of freedom of these molecules in combustion of hydrocarbon fuels (even in the presence of shock waves or in the detonation mode of combustion) could be assumed with good accuracy to be thermodynamically equilibrium. The measurements of the times of vibrational relaxation in a CH 4 molecule [18,19], however, show that this assumption can prove to be invalid. Therefore, a finite time of vibrational-translational relaxation in a CH 4 molecule was taken into account in constructing the thermally nonequilibrium model of chemical kinetics.…”
Section: Formulation Of the Problem And Kinetic Modelmentioning
confidence: 96%
See 3 more Smart Citations
“…It was believed until recently that vibrational relaxation in hydrocarbon molecules proceeds rather rapidly, and the translational, rotational, and vibrational degrees of freedom of these molecules in combustion of hydrocarbon fuels (even in the presence of shock waves or in the detonation mode of combustion) could be assumed with good accuracy to be thermodynamically equilibrium. The measurements of the times of vibrational relaxation in a CH 4 molecule [18,19], however, show that this assumption can prove to be invalid. Therefore, a finite time of vibrational-translational relaxation in a CH 4 molecule was taken into account in constructing the thermally nonequilibrium model of chemical kinetics.…”
Section: Formulation Of the Problem And Kinetic Modelmentioning
confidence: 96%
“…, L), the combinatorial states are denoted by lν i + kν j , and the energies of different states are given in brackets in Kelvin degrees. For the CH 4 molecule, the rate constants of the processes CH 4 (A) → CH 4 (B) (k AB ), CH 4 (B) → CH 4 (C) (k BC ), and CH 4 (C) → CH 4 (G) (k CG ) were measured in [18] at T = 300 K. The measurements showed that k AB ≈ k BC k CG . The characteristic times of these processes at atmospheric pressure are τ AB = 2.6 nsec, τ BC = 2.2 nsec, and τ CG = 1.5 μsec.…”
Section: Formulation Of the Problem And Kinetic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, at low internal energies, detailed studies are much more common, leading to a consistent physical picture of inelastic processes in this regime. 8,[19][20][21] NO 2 has also been the subject of numerous non-state-resolved spectroscopy based energy transfer measurements at quite high internal energies for nearly 2 decades, [22][23][24][25][26] but in these experiments the resolution was not sufficient to separate rotational energy transfer from the overall relaxation of the molecule.…”
Section: Introductionmentioning
confidence: 99%